The Community Service: Early Detection of Non-Communicable Disease Risk Factors (PTM) in Students and Lecturers at STIKes Widya Dharma Husada Tangerang: Pengabdian Masyarakat : Deteksi Dini Faktor Resiko Penyakit Tidak Menular (PTM) Pada Mahasiswa dan Dosen di STIKes Widya Dharma Husada Tangerang - Andriati, Riris; Rahayu, Savitri; Listiana, Ida; Pratiwi, Rita Dwi; Veri, Veri; Darmayanti, Desy; Ayuningtyas, Gita; Pratama, Yusuf Apriliyansyah Pratama; Sania, Sania; Husniati, Siti; Bima, Bima; Frili, Frili; Dewi, Bunga Arista (Ruang Ide Publisher, 2022)
Abstract Non-Communicable Diseases (NCD) is a catastrophic disease with the highest cause of death in Indonesia. This results in the loss of productive days for sufferers and caregivers. Research conducted by the Health Research and Development Agency shows that the current development of PTM in Indonesia is increasingly worrying. The reason is the increasing trend of PTM is followed by a shift in disease patterns, if in the past, this type of disease was usually experienced by the elderly group, now it is starting to threaten the productive age group. Physical examination which includes blood pressure, blood sugar examination, measurement of weight, height, waist circumference can be an indicator to determine physical fitness. Anemia also affects a person's nutritional status. The incidence of anemia in Indonesia is still quite high. The solution to overcome this problem is carried out by community service activities by lecturers and students with the target of lecturers and students in the environment at STIKes Widya Dharma Husada Tangerang. The implementation of this community service is carried out with the following methods: Blood pressure checks, blood sugar checks, weighing, measuring height, waist circumference, health counseling and giving blood-supplement tablets (TTD) for free to students. By holding this service activity, it is hoped that it can trigger the awareness of students to care more about health, routinely check health and assist government programs in reducing the incidence of anemia and also the risk of non-communicable diseases (PTM) in the community. The follow-up to the results of this community service is that health checks, health counseling and the provision of Blood Add Tablets (TTD) can be carried out in different places so that more teenagers understand the importance of health and can reduce the incidence of anemia in Indonesia, especially in Banten Province. Keywords: health checks, non-communicable diseases, blood pressure, blood sugar levels, blood-added tablets